The Correlation between Student Perception and Learning Motivation: Blended Learning Strategy - Abednego Abednego; Sefnath Nuniary; Emma Rumahlewang; John Rafafy Batlolona (AL-ISHLAH: Jurnal Pendidikan, 2023)
Different perceptions will affect the success of learning outcomes, namely student perceptions. Thus, it affects student learning motivation. The study aimed to determine the relationship between student perceptions and learning motivation toward blended learning strategy (BLS). The research used is a correlational test between student perceptions and learning outcomes with BLS. The participants in this study were 70 people from two different classes. The BLS research instruments and student learning motivation include 1) Desire to succeed, 2) Encouragement and needs in learning, 3) Expectations and future goals, and 4) Appreciation of learning. 5) Interesting desires in learning, 6) A Conducive learning environment. The results showed no relationship between student perceptions and learning motivation toward BL learning strategies. Thus, other factors influence student perceptions and learning motivation, such as socioeconomic, family environment, and cultural environment. The implications of this research can provide insights for education policy makers in Indonesia and in the regions about how to design policies mixed learning that is aligned with the preferences of teachers and students in improving the quality of learning and student learning outcomes.